Potential regions in the Persian Gulf to deploy offshore floating photovoltaic systems. Issue 3 (9th August 2020) - Honnur Vali, Mohamed Shaik; Gupta, Naren; Goh, Keng; Umar, Tariq
Abstract : Generating energy by means of renewable sources is a vital strategy for all the Gulf Cooperation Council (GCC) countries. Photovoltaic (PV) systems in the GCC have been a primary choice among renewable sources due to regional weather and high levels of irradiance. However, unfavourable environmental factors such as high temperatures, soiling and dust have been a concern for PV performance. Offshore PV systems can provide a solution to mitigate these issues and improve system performance. Thus far, floating PV (FPV) systems have remained unexplored in the GCC region. This paper identifies and presents six potential regions in the GCC in which FPV systems could be deployed based on three environmental factors.